Addition of water to an alcoholic RAFT PISA formulation leads to faster kinetics but limits the evolution of copolymer morphology. Issue 4 (8th December 2015) - Jones, E. R.; Semsarilar, M.; Wyman, P.; Boerakker, M.; Armes, S. P.
Abstract : Addition of water leads to a much faster rate for the RAFT dispersion polymerization of benzyl methacrylate in ethanol, enabling degrees of polymerization of up to 1500 to be achieved. Abstract : RAFT dispersion polymerization of benzyl methacrylate (BzMA) has been used previously (E. R. Jones, et al., Macromolecules, 2012, 45, 5091) to prepare poly(2-(dimethylamino)ethyl methacrylate)-poly(benzyl methacrylate) (PDMA–PBzMA) diblock copolymer nanoparticles in ethanol via polymerization-induced self-assembly (PISA). However, the rate of polymerization was relatively slow, with incomplete monomer conversions being obtained when targeting higher mean degrees of polymerization (DP) even after 24 h at 70 °C. Herein we examine the effect of the addition of up to 20% w/w water co-solvent on the kinetics of BzMA polymerization for this PISA formulation. Significantly faster polymerizations were observed: for a target DP of 200, 90% BzMA conversion was achieved within just 6 h in the presence of 20% w/w water, compared to only 35% conversion in anhydrous ethanol under the same conditions. This rate enhancement enables much higher mean DPs to be obtained for the core-forming PBzMA and is attributed to greater partitioning of the BzMA monomer within the particles, which increases the local monomer concentration. However, the presence of water adversely affected the evolution of copolymer morphology from spheres to worms to vesicles when employing a relatively short PDMA chain transfer agent, with only kinetically-trapped spheres being obtained at higher levels of added water. Aqueous electrophoresis studies indicate that the PDMA stabilizer chains acquired partial cationic charge in the presence of water. This leads to more efficient inter-particle repulsion, thus preventing the sphere-sphere fusion events required for an evolution in morphology. In summary, the addition of water to such PISA formulations allows the more efficient synthesis of spherical nanoparticles, but should be used with caution if either diblock copolymer worms or vesicles are desired.